Effect of aqueous and alcoholic extracts and essential oil of Artemisia herba alba on some types of bacteria resistant to antibiotics - Iman Daw Amhamed; Mona Shaban Kremid (African Journal of Advanced Pure and Applied Sciences, 2026)
This study aimed to evaluate the effect of Artemisia herba alba extracts (aqueous, alcoholic and essential oil) on antibiotic-resistant bacteria. In which four types were tested, namely Staphylococcus aureus (MRSA) Staphylococcus epidermidis, Klebsiella pneumoniae, Klebsiella oxytoca, using the diffusion disk method and concentrations (100, 200, 300 mg/ml) for the aqueous and alcoholic extract, while the essential oil was used in its pure form. The most effective antibacterial activity was observed for the essential oil of plant with an inhibition diameter from 8.00±0.00 to 11.33±1.52 mm, and its aqueous extract effect on bacteria MRSA and S. epidermidis was 8.66±1.52 and 8.33±0.57 mm, respectively, at 300 mg/ml. The inhibitory effect of alcoholic extract was 10.00±0.00 mm at 300 mg/ml for MRSA as for S. epidermidis at the same concentration had high inhibition diameter 13.66±1.15 mm. Phytochemical screention of aqueous extract revealed the presence of phenols and saponins, whereas, alcoholic extract revealed the presence of phenols, tannins, terpenoids and saponins. The chemical components of the essential oils were determined by GC-MS device. The main compounds of A. herba alba were Camphor (30.527%), Thujone (22.471%) and Camphene (10.291%). These results suggest that essential oil extract can be considered as a potential source of antibacterial compounds.